2016
DOI: 10.1016/j.wneu.2016.07.101
|View full text |Cite
|
Sign up to set email alerts
|

The DERIVO Embolization Device in the Treatment of Intracranial Aneurysms: Short- and Midterm Results

Abstract: The DED seems effective and safe in the treatment of different kinds of intracranial aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 31 publications
2
45
0
Order By: Relevance
“…However, we did not observe any incidence of major ischemic stroke and only one case was associated with persistent aphasia (mRS 1). These results are in line with the findings by Akgul et al who reported thromboembolic events in 8.3% and the absence of major ischemic stroke in patients treated with the first-generation DED 13. They only mentioned one case (4.2%) with stent stenosis that was associated with mild hemiparesis (mRS 1).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, we did not observe any incidence of major ischemic stroke and only one case was associated with persistent aphasia (mRS 1). These results are in line with the findings by Akgul et al who reported thromboembolic events in 8.3% and the absence of major ischemic stroke in patients treated with the first-generation DED 13. They only mentioned one case (4.2%) with stent stenosis that was associated with mild hemiparesis (mRS 1).…”
Section: Discussionsupporting
confidence: 92%
“…The only clinical study to date was published by Akgul et al 13. The authors analyzed the immediate and short-term clinical and angiographic results mainly of the first-generation DED in 24 patients with 36 aneurysms and reported a morbidity rate of 4.2% within the first 30 days after treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A further explanation for the potentially lowered thrombogenicity of the DED may be related to its thin blueish surface layer of oxides and oxynitrides (BlueXide), which reduces the friction during delivery of the device 13. Preclinical studies indicated a reduced thrombogenic potential of the DED 14 15.…”
Section: Discussionmentioning
confidence: 99%
“…The Acandis Derivo Embolization Device (DED, Acandis, Pforzheim, Germany) is a new self-expandable FDD composed of 48 nitinol composite wires with a radiopaque platinum core and three additional platinum–iridium markers at both ends to enhance its visibility on X-ray imaging 13. Moreover, the DED is provided with a thin surface layer of titanium oxides and oxynitrides.…”
Section: Introductionmentioning
confidence: 99%